Cervical adenitis mimicking a bacterial cervical abscess in an infant with incomplete Kawasaki disease and coronary aneurysm: A case report - Atamari-Anahui, Noé (2021)
Background: Kawasaki disease (KD) is an acute and self-limited vasculitis common in children under five years. The diagnosis is a challenge in children under six months of age. Report case: We report a three-month-old infant with fever and a painful neck tumor of three days of disease. He was diagnosed with an abscessed cervical mass and received antibiotic treatment for ten days. During hospitalization, macular erythematous lesions developed throughout the body, persistence of fever, and elevated inflammatory markers. Echocardiography was performed, finding dilatation of the coronary arteries, being diagnosed with incomplete KD. He received intravenous human immunoglobulin and acetylsalicylic acid. He is currently undergoing cardiology controls with acetylsalicylic acid due to persistent dilatation of the coronary arteries. Conclusions: Cervical adenitis can mimic other skin infections such as cervical abscesses. It can cause a delay in the diagnosis of KD, producing complications such as a coronary aneurysm.